Pengaruh Hypnoteaching dalam Problem-Based Learning terhadap Kemampuan Komunikasi Matematis Siswa - Ega Edistria (Jurnal Inovasi Pendidikan Dasar, 2016)
This study examined the application of hypnoteaching in problem based learning (PBL) to the junior high school student’s mathematical communication ability. This study used design research a static group comparison of two experimental groups. First experiment received PBL without hypnoteaching. Second experiment received PBL and hypnoteaching. This study was tested to grade seventh junior high school students with quasi experimental method. The result of this study showed that there are differences the mathematical communication abilities between students who obtained hypnoteaching in PBL and students who didn’t obtain hypnoteaching in PBL.